2022
DOI: 10.3389/fsurg.2022.860806
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-related lncRNA signature predicts prognosis and immunotherapy efficacy in cutaneous melanoma

Abstract: PurposeFerroptosis-related lncRNAs are promising biomarkers for predicting the prognosis of many cancers. However, a ferroptosis-related signature to predict the prognosis of cutaneous melanoma (CM) has not been identified. The purpose of this study was to construct a ferroptosis-related lncRNA signature to predict prognosis and immunotherapy efficacy in CM.MethodsFerroptosis-related differentially expressed genes (FDEGs) and lncRNAs (FDELs) were identified using TCGA, GTEx, and FerrDb datasets. We performed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Xu et al. created a novel signature based on five lncRNAs, including AATBC, AC145423.2, LINC01871, AC125807.2 and AC245041.1, that can predict the clinical outcome in melanoma patients 34 . Also, Ma et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al. created a novel signature based on five lncRNAs, including AATBC, AC145423.2, LINC01871, AC125807.2 and AC245041.1, that can predict the clinical outcome in melanoma patients 34 . Also, Ma et al.…”
Section: Discussionmentioning
confidence: 99%
“…Also, different studies on TCGA and GEO databases have demonstrated that additional lncRNAs, including PRRT3‐AS1, 26 DANCR 26 and FOXD2‐AS1, 31 are related to clinical outcomes and melanoma progression. Additionally, several studies have introduced lncRNA‐based models for predicting clinical outcomes in uveal and cutaneous melanoma patients 26,32–35 . Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of SUCLG2-AS1 is associated with better OS in clear cell renal cell carcinoma and triple-negative breast cancer(31, 32). High expression of AC245041.1 is a poor prognostic factor in patients with gastric adenocarcinoma and cutaneous melanoma (15,33). High expression of AC019080.5 is a risk factor for poor OS in patients with endometrial cancer (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are involved in the mechanisms of OC progression, including carcinogenesis, proliferation, migration, invasion, metastasis, and angiogenesis (10,14). Evidence has shown that lncRNAs can participate in the development, recurrence, and response to OC immunotherapy by regulating multiple pathways, such as ferroptosis (15), autophagy (16), pyroptosis (17), necroptosis (18).…”
Section: Introductionmentioning
confidence: 99%
“…AC125807.2 was identified to be part of a network of competing endogenous RNA networks, also including TMPO-AS1 (red module; only correlated with HDIR), to regulate FAM82B expression in lung adenocarcinoma, leading to poor prognosis ( 49 ) and was overexpressed in cutaneous melanoma ( 50 ). Moreover, AC125807.2 was presented as part of a list of 14 immune-related lncRNAs which were associated with clinical outcomes in melanoma patients ( 51 ) and discussed as potentially involved in ferroptosis ( 52 ). Ferroptosis regulates cell death via lipid peroxidization, thus posing as a mechanism for tumor suppression.…”
Section: Discussionmentioning
confidence: 99%